Use of Team Sports in Physical Education Activities in Preschool Educational Organizations in Our Country and Abroad - Barno Pulatovna Abdullaeva (Periodica Journal, 2022)
The article discusses the effectiveness of teaching the first elements of football to students of educational institutions in the pre-school education system and the development of effective methods for this. In recent years, physical education in preschool educational organizations has been implemented according to the "Ilk Kadam" single program. Today, the preschool education system is going through a period of serious changes. This is primarily related to the economic and social changes taking place in society. The constantly increasing influence of various negative factors on the human body leads to the deterioration of health and a decrease in the physical and mental potential of children. The increase in the requirements for preparing a child for school has led to a decrease in physical activity due to the increase in hours allocated for intellectual development. In order to solve these problems, the article discusses new methods for organizing active physical activity of children from preschool age
Keywords: Preschool education; child organism; coordination ability; football elements